Population dynamics and management of mango fruit fly, bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Akhila M U (Department of agricultural entomology, College of agriculture, 2015)
The investigation entitled “Population dynamics and management of mango fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae)” was conducted at the College of Agriculture, Vellayani during 2013-2015. The main objective of the work was to study the host range and population dynamics of mango fruit fly and to standardize the use of alternate chemicals in Bait Application Technique (BAT) and Male Annihilation Technique (MAT) for its management. A survey was conducted in twenty homesteads of Kalliyoor panchayath having at least 25 cents and the Instructional Farm, Vellayani during 2013-2015 to study the pest incidence, extent of damage and host range of mango fruit fly. Study revealed the incidence of the B. dorsalis in three fruit crops viz., mango, guava and banana, out of the five selected. No infestation was observed in papaya and sapota. B. dorsalis preferred soursop as one of its hosts. The species emerged from mango were identified as B. dorsalis and B. caryeae (Kapoor). In guava and banana, only infestation by B. dorsalis was recorded. Infestation by other species of fruit fly was also recorded from rose apple and solanaceous vegetables viz., brinjal and tomato and the species were identified as B. syzigi and B. latifrons (Hendel), respectively. Fruit fly infestation in brinjal and tomato are new reports from Kerala. The percentage infestation in mango was higher in peak fruiting season during May (49.28) to June (61.68) and the maximum number of maggots was observed during June 2014 (82.49). Studies were conducted at ten homesteads of Kalliyoor panchayath and the Instructional Farm, Vellayani to monitor the population fluctuation and species diversity of fruit flies using methyl eugenol traps during 2014-15. It revealed the prevalence of four Bactrocera spp. viz., B. dorsalis, B. caryeae, B. correcta (Bezzi) and B. zonata (Saunders) with a species composition of 28.74, 69.85, 1.38 and 0.02 per cent, respectively. The population of B. caryeae (278.91) and B. dorsalis (124.82) reached the peak level in June 2014 which coincided with the peak fruiting season of mango. Studies on correlation with weather parameters revealed that the maximum temperature, average relative humidity and sunshine hours had a significant positive correlation with the population of B. dorsalis and B. caryeae. The biology of B. dorsalis in different mango varieties and hosts was studied. Longer pupal period (11.40 days) and maximum adult longevity (20.70 days) were observed in the mango variety Bangalora. Among the different hosts, the highest larval (12.90 days) and pupal periods (10.30 days) were recorded in banana. However, the highest adult longevity (19.70 days) was observed in mango. Field studies indicated that the activity of B. dorsalis was more (6.92 flies per trap) during 6.00 to 8.00 am. Based on the percentage mortality and LT 50 values, 10 per cent jaggery along with lambda cyhalothrin 0.005%, 10 per cent jaggery along with spinosad 0.02%, 10 per cent jaggery along with malathion 0.1% and 10 per cent jaggery along with lambda cyhalothrin 0.0025% in BAT and alcohol, lure and spinosad (6: 4: 0.2 v: v: v), alcohol, lure and malathion (6: 4: 1 v: v: v), alcohol, lure and spinosad (6: 4: 0.02 v: v: v) and alcohol, lure and deltamethrin (6: 4: 0.4 v: v: v) in MAT were selected for field evaluation. Field studies conducted in homesteads of Balaramapuram panchayath using the above promising insecticides revealed that 10 per cent jaggery along with spinosad 0.02% was effective in BAT and alcohol, lure and spinosad (6: 4: 0.2 v: v: v) was the best treatment in MAT. The study revealed that in addition to B. dorsalis, B. correcta and B. zonata and many other fruit fly species including B. caryeae, B. syzigi and B. latifrons are also becoming a great threat to crops. Considering the environmental factors, spinosad can be selected as an alternative chemical for the conventional organophosphate insecticide, malathion.